The New Edition between the history of science and the history of scientific thought: some editorial practices in nineteenth-century linguistics. (Prassi Ecdotiche della Modernità Letteraria, 2022)
The paper aims to highlight that the study of ecdotical practices in the history of language science reveals evolutionary paths in the history of linguistic science and of linguistic thought. A few emblematic cases belonging to 19th-century linguistics demonstrate not only that the comparison of successive editions of foundational texts is revealing of extensions of the linguistic domains that can be referred to further analysis of data, but also that evolution in the reflection on general principles can characterise a new edition. The historiographical and interpretative value of translations is also considered.
Keywords: editorial practices; History of linguistics; History of linguistic thought; New edition; Translation